Stet Again! More Tricks of the Trade for Publications People: Selections from 'The Editorial Eye' - Jill Steffey (Journal of Applied Communications, 1998)
A review of Stet Again! More Tricks of the Trade for Publications People: Selections from 'The Editorial Eye' by Linda B. Jorgensen.